Penerapan Metode Promethee pada Sistem Pendukung Keputusan dalam Pemilihan Duta Wisata Kabupaten Deli Serdang - Cici Alfiani Pradika Dita; Nelly Astuti Hasibuan; Dito Putro Utomo (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Tourism ambassadors are one of the means for one region to promote what tourism potential is owned by each region, especially the Deli Serdang regency area. With the existence of tourism ambassadors, it is hoped that there will be a figure or role who is able to become a promoter and be able to promote the tourism potential in the area well. The event for the selection of tourism ambassadors as a means of developing the potential talents, creativity, intelligence of the younger generation to become figures who can play a role in promoting the richness of art, culture and tourism. To help identify or select a decision support system using the PROMETHEE (Preference Ranking Organization Method for Enricment Evalution) method. Promethee is a method for solving a decision-making case to solve a decision-making case that falls into the MCDM (Multi-Criteria Decision Making) category with the principle of outranking. After using the promethee method, a ranking of each alternative can be obtained. Alternatives A3 and A4 "M Sakha Admaja" and "Nabila Putri Ramadhani".